Enhancing performance of building elements with phase change materials for cooling with air-based systems. (July 2022) - Zavrl, Eva; El Mankibi, Mohamed; Dovjak, Mateja; Stritih, Uroš
Abstract: The present literature review addresses how to enhance the overall performance of phase change material (PCM) integrated into building elements for cooling with nighttime ventilation. The review consists of the introduction describing the issue of overheating of buildings in summer with possible solutions. The second section gathers the improved PCM discharge cycles by total volume nighttime natural and/or mechanical ventilation. The third section focuses on ventilated building elements (roof with photovoltaics, ceiling, floor, façade, internal wall, glazed façade element and facade with build-in photovoltaics). Finally, the conclusions are summarized based on the reviewed studies, followed by the table of reviewed work. Highlights: The PCM integrated building elements with total volume nighttime ventilation are reviewed. The total volume nighttime ventilation flow rates and duration are analysed. Locally ventilated building elements are summarized in groups based on the element type. The melting temperatures of PCM in locally ventilated building elements are presented.